The peach keeper : a novel - Allen, Sarah Addison (Bantam Books, 2011)
Willa Jackson of Walls of Water, North Carolina, has lately learned that an old classmate--socialite do-gooder Paxton Osgood--of the very prominent Osgood family, has restored her family's Blue Ridge Madam home to its former glory, with plans to open a top-flight inn. But when a skeleton, found buried beneath the lone peach tree on the property is found, Willa and Paxton must confront the dangerous passions and tragic betrayals that once bound their families.